Use of Aptamers as Diagnostics Tools and Antiviral Agents for Human Viruses - Víctor M. González; M. Elena Martín; Gerónimo Fernández; Ana García-Sacristán (MDPI AG, 2016)
Appropriate diagnosis is the key factor for treatment of viral diseases. Time is the most important factor in rapidly developing and epidemiologically dangerous diseases, such as influenza, Ebola and SARS. Chronic viral diseases such as HIV-1 or HCV are asymptomatic or oligosymptomatic and the therapeutic success mainly depends on early detection of the infective agent. Over the last years, aptamer technology has been used in a wide range of diagnostic and therapeutic applications and, concretely, several strategies are currently being explored using aptamers against virus proteins. From a diagnostics point of view, aptamers are being designed as a bio-recognition element in diagnostic systems to detect viral proteins either in the blood (serum or plasma) or into infected cells. Another potential use of aptamers is for therapeutics of viral infections, interfering in the interaction between the virus and the host using aptamers targeting host-cell matrix receptors, or attacking the virus intracellularly, targeting proteins implicated in the viral replication cycle. In this paper, we review how aptamers working against viral proteins are discovered, with a focus on recent advances that improve the aptamers' properties as a real tool for viral infection detection and treatment.